Molecular Survey of Tularemia and Plague in Small Mammals From Iran - Mostafavi, Ehsan; Ghasemi, Ahmad; Rohani, Mahdi; Molaeipoor, Leila; Esmaeili, Saber; Mohammadi, Zeinolabedin; Mahmoudi, Ahmad; Aliabadian, Mansour; Johansson, Anders (Frontiers in Cellular and Infection Microbiology, 2018)
Introduction: Plague and tularemia are zoonoses and their causative bacteria are circulating in certain regions of Iran. This study was conducted to investigate potential disease reservoirs amongst small wildlife species in different regions of Iran. Methods: Rodents, insectivores and hares from seventeen different provinces of the country were collected in 2014 and 2015. Samples were taken from the spleens of the animals and Real-time PCR was applied to detect nucleic acid sequences that are specific to Francisella tularensis and Yersinia pestis, respectively. Results: Among 140 collected rodents, 25 distinct species were identified out of which five were the most common: Microtus paradoxus (21% out of 140 rodents), Apodemus witherbyi (12%), Microtus irani (11%), Mus musculus (11%) and Microtus socialis (10%). Seventeen insectivores were collected and identified as Crocidura suaveolens (82%) and C. leucodon (18%). Fifty-one hares were collected and identified as Lepus europaeus (57%), Lepus tolai (14%) and Lepus sp. (29%). Three out of 140 rodents (1.91%) tested positive for F. tularensis, an A. witherbyi, a Mus macedonicus, and a Chionomys nivalis collected from Golestan, Khuzestan and Razavi Khorasan provinces, respectively. Two hares (3.92%) were F. tularensis-positive, a L. europaeus from Khuzestan and a Lepus sp. from the Sistan and Baluchistan province. None of the animals tested positive for Y. pestis. Conclusion: This is the first report of direct detection of F. tularensis in mammals of Iran and the first-time observation of the agent in a snow vole, C. nivalis worldwide. The results indicate that tularemia is more widespread in Iran than previously reported including the Northeast and Southwestern parts of the country. Future studies should address genetic characterization of F. tularensis positive DNA samples from Iran to achieve molecular subtyping and rule out assay cross-reactivity with near neighbor Francisella species.